Evaluating the supervision tools of the Central Bank of Iraq to verify the continuity of private banks: An applied research in the Central Bank of Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The aim of the research to highlight the calendar of the most important tools used by the Central Bank of Iraq, in the implementation of the function of supervisory oversight, to verify the stability of the banking system, and protect the funds of shareholders, and depositors in general and the absence of any raises the risks of default and financial failure in particular, for commercial banks. The most important flaws and weaknesses in these tools, in the early detection of the risks of continuity in a timely manner, The study concluded a set of conclusions, including the weakness of the tools used in the performance of the function of supervisory oversight in detecting cases of default and financial failure in the early time as well as the protection of the financial system of banking, in addition to a set of recommendations, including the need to develop and review the tools used in Performance of supervisory control function in a manner that contributes to the detection of bank failures in a timely manner.